MODEL PERANCANGAN APLIKASI PENELUSURAN ALUMNI BERBASIS WEBSITE - Effendy, Dedi Usman; Suswanto, Budi (DINAMIKA DOTCOM, 2014)
Alumni tracking information system applications is one of the alumni of information search source on line by using a database. With 4 menu options that must be filled to the database are: personal history, educational history, employment history, and suggestions or questionnaires, also provide joint chat as a medium of communication between fellow alumni on this web system. The software used in these applications include the operating system the web server, database server, and web programming. For the Windows operating system in use, for use apache web server, to the database servers in use MySQL, and PHP web programming is used, then use the application to display the browser Internet Explorer, Opera, or other web browser.The purpose of this research is to design and create application programs that can facilitate the academic community in obtaining information about tracing graduates / alumni of the search-based website.Outcomes of this study are expected to form an alumni tracking design of new systems with facilities that support both the needs of the campus as well as to support the needs of the alumni themselves, from Alumni Search program, there are several options page, among others: the Home page, Registration page, Contact page, the page news archives and also a control panel where there are pages and pages Searching Event.Â Keywords: Search Alumni, Database, PHP, MySQL, Web